MAKING WEB SITE USING ACTIVE SERVER PAGES (ASP) ONLINE BOOK SHOP ON THROUGH THE INTERNET MEDIA - Apriani Apriani; Ir. Aqwam Rosadi Kardian, MM Ir. Aqwam Rosadi Kardian, MM (Jurnal Sistem Informasi, 2001)
Internet technology is no longer a sentence that is foreign to people in the world ofcomputers. Even for the layman though, those words the world wide web as if it hadbecome an inseparable part of modern human life today.It is not unreasonable if current human agents tend to choose the web as a conduit ofinformation. With the increasingly complex needs, no longer be easy to create a website interesting and informative is only by using HTML. But something more isneeded so that user interaction can be used as the controlling information coming.Therefore, the author tries to discuss about the server-based programming ActiveServer Pages (ASP). ASP is a technology that allows developers to work on processeswithin the server.For a discussion of the ASP, was selected for the bookstore application. Hence madea website about pemesananbuku bookstore featuring an online, catalog and guestbook of the facilities offered by using Active Server Pages (ASP).